Dronabinol and lofexidine for cannabis use disorder: A randomized, double-blind, placebo-controlled trial. (1st February 2016) - Levin, Frances R.; Mariani, John J.; Pavlicova, Martina; Brooks, Daniel; Glass, Andrew; Mahony, Amy; Nunes, Edward V.; Bisaga, Adam; Dakwar, Elias; Carpenter, Kenneth M.; Sullivan, Maria A.; Choi, Jean C.
Highlights: One of the few large placebo-controlled treatment trials for cannabis dependence. Participants were randomized to receive dronabinol plus lofexidine or placebo. There was not a significant effect of treatment on achieving cannabis abstinence. There was not a significant effect of treatment on withdrawal scores across time. The intervention did not show promise as a treatment for cannabis use disorder. Abstract: Background: Cannabis use disorder is associated with substantial morbidity and, after alcohol, is the most common drug bringing adolescents and adults into treatment. At present, there are no FDA-approved medications for cannabis use disorder. Combined pharmacologic interventions might be particularly useful in mitigating withdrawal symptoms and promoting abstinence. Objective: The purpose of this study was to evaluate the safety and efficacy of dronabinol, a synthetic form of delta-9-tetrahydrocannabinol, a naturally occurring pharmacologically active component of marijuana, and lofexidine, an alpha-2 agonist, in treating cannabis dependence. Methods: One hundred fifty six cannabis-dependent adults were enrolled and following a 1-week placebo lead-in phase 122 were randomized in a double-blind, placebo-controlled, 11-week trial. Participants were randomized to receive dronabinol 20 mg three times a day and lofexidine 0.6 mg three times a day or placebo. Medications were maintained until the end of week eight, were then tapered over two weeks and patients were monitored off medications during the last study week. All participants received weekly motivational enhancement and relapse prevention therapy. Marijuana use was assessed using the timeline follow-back method. Results: There was no significant difference between treatment groups in the proportion of participants who achieved 3 weeks of abstinence during the maintenance phase of the trial (27.9% for the medication group and 29.5% for the placebo group), although both groups showed a reduction over time. Conclusions: Based on this treatment study, the combined intervention did not show promise as a treatment for cannabis use disorder.